2009
DOI: 10.2337/dc09-0425
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Numeracy

Abstract: OBJECTIVEUnderstanding the reasons and eliminating the pervasive health disparities in diabetes is a major research, clinical, and health policy goal. We examined whether health literacy, general numeracy, and diabetes-related numeracy explain the association between African American race and poor glycemic control (A1C) in patients with diabetes.RESEARCH DESIGN AND METHODSAdults with type 2 diabetes (n = 383) were enrolled in a cross-sectional study at primary care and diabetes clinics at three medical centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
108
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 22 publications
1
108
0
4
Order By: Relevance
“…Nonetheless, African-Americans with chronic kidney disease are less likely to be seen by a nephrologist, more likely to progress to ESRD, and less likely to be listed for or receive a renal transplant (48). Moreover, there is evidence from studies in patients with other chronic diseases that health literacy mediates racial disparities in health outcomes (49,50). This suggests that efforts to improve health literacy among racial minorities and sociodemographically disadvantaged patients, including veterans, with chronic renal disease and ESRD may be a means to reduce health disparities and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, African-Americans with chronic kidney disease are less likely to be seen by a nephrologist, more likely to progress to ESRD, and less likely to be listed for or receive a renal transplant (48). Moreover, there is evidence from studies in patients with other chronic diseases that health literacy mediates racial disparities in health outcomes (49,50). This suggests that efforts to improve health literacy among racial minorities and sociodemographically disadvantaged patients, including veterans, with chronic renal disease and ESRD may be a means to reduce health disparities and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an adjusted analysis that excluded health literacy, African Americans were 2.4 times more likely to be non-adherent to their HIV medication regimen than whites (95% confidence interval [CI] ¼ 1.14-5.08). When health literacy was included in the final model adjusting for relevant covariates, the effect estimates of race Promoting Health Literacy Researchdiminished to non-significance and health literacy remained a significant independent predictor of non-adherence (adjusted odds ratio [AOR] ¼ 2.12, 95% CI ¼ 1.93-2.32) (Osborn, Paasche-Orlow, Davis, & Wolf, 2007). In another study, patients were asked their preferences regarding end-of-life care if they would develop advanced dementia.…”
Section: Integrate Health Literacy Assessment In Disparities Researchmentioning
confidence: 99%
“…The consequences of early failures in education have more recently been linked to problems in healthcare. Research has begun to emerge showing how a health literacy skill set is linked to a range of health outcomes, and evidence has also emerged demonstrating how deficits in these skills possibly explain certain disparities (Bennett, 2009;Osborn, Cavanaugh, Wallston, White, & Rothman, 2009;Osborn, Paasche-Orlow, Davis, & Wolf, 2007;Sentell, 2006;Waldrop-Valverde, 2010;Wolf, 2006).…”
mentioning
confidence: 99%
“…7 A number of studies have suggested that health literacy may be an important factor in mediating health disparities. [8][9][10] Health equity is a universal principle in the American Academy of Pediatrics agenda for children. The Academic Pediatric Association's vision and strategic plan emphasize an "equitable children's health agenda."…”
mentioning
confidence: 99%